An analysis of the structure of knowledge and students' construction of knowledge in an introductory accounting course - Myers, Lyndrianne Peta (Rhodes University, Faculty of Education, Centre for Higher Education Research, Teaching and Learning, 2014)
This research seeks to explain how students construct knowledge in introductory accounting. It was prompted by concerns over low pass rates for first-year Introductory Accounting students at Rhodes University and particularly low pass rates amongst novice (first-time) Accounting Students. In trying to get a better understanding of reasons behind these pass rates, this research focuses on the structure of knowledge in the discipline and what this means for how students should construct knowledge in the course. Bernstein's Pedagogic Device and the dimensions of Semantics and Specialisation in Maton's Legitimation Code Theory are used as theoretical and analytical frameworks to help understand the structure of knowledge in this course, how knowledge is recontextualised and finally how it is acquired by students. A group of students from the 2011 class were interviewed to gain a better understanding of how each of these students constructed knowledge during the semester. The analysis of these interviews reveals how students construct knowledge in the course and the implications this has for their success over the semester. Analysing this interview data, and comparing it with the levels of success for each student, permitted me to develop an improved understanding of how successful and unsuccessful students construct knowledge. As a teacher of Accounting, understanding and being explicit about the structure of knowledge in the discipline, and how this impacts on the construction of knowledge, will allow me to advise future students on how to most effectively construct knowledge in this course and to advise and guide colleagues on how best to present this course.
Keywords: Knowledge, Theory of; Learning, Psychology of; Accounting -- Study and teaching (Higher) -- South Africa -- Grahamstown